PSYCHO-EMOTIONAL CHANGES IN PATIENTS WITH TUBERCULOUS SPONDYLITIS - Alimova Gulrukh Salimovna (Web of Journals Publishing, 2025)
The article discusses psycho-emotional changes occurring in patients with tuberculous spondylitis. Tuberculous spondylitis is an infectious disease affecting the spine, and in addition to physical discomfort, it significantly affects the psychological state of patients. The main focus is on how this disease can cause depression, anxiety and other emotional disorders in patients. Possible mechanisms of these changes are discussed and the importance of an integrated approach to treatment, including psychological support, is emphasized.
Keywords: Tuberculous spondylitis, psycho-emotional changes, depression, psychological support.